A 10-year follow-up study on suicidal mortality after 1999 Taiwan earthquake. (August 2016) - Chen, Sam Li-Sheng; Lee, Chau-Shoun; Yen, Amy Ming-Fang; Chen, Hsiu-Hsi; Chan, Chang-Chuan; Chiu, Sherry Yueh-Hsia; Fann, Jean Ching-Yuan; Chang, Jung-Chen
Abstract: Objective: The long-term impact of natural disasters on suicide in general population and survivors remains uncertain. The present report examined the direction and the length of the influence of an earthquake over suicide across age groups. Method: We used an interrupted time-series design with non-equivalent no-treatment group to evaluate post-earthquake changes in suicide rates by the standardized mortality ratio. Results: The time trend changes in suicide rates before and after the earthquake were similar for males and females but different between senior and junior age groups. Gender-specific relative ratios were 0.85 (95%CI: 0.81–0.90) for males and 0.79 (95% CI: 0.72–0.86) for females. Age-gender-stratified relative ratios were 0.61 (95% CI: 0.53–0.70) and 0.69 (95% CI: 0.64–0.75) for males and females aged less than 45 years, respectively. Although the overall suicide mortality increased after the earthquake, the relative suicide risk ratio decreased 31–39% for those aged less than 45 years, which persisted for nearly 10 years after earthquake. Conclusion: Our study demonstrated that a severe earthquake resulted in a significant decrease in standardized suicide mortality ratios in exposed areas for 10 years compared to unexposed area, particularly in a younger population.